2018
DOI: 10.3389/fncel.2018.00410
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Müller Glia Conversion Into Retina Ganglion Cells Using Neurogenin2

Abstract: Degenerative retinopathies are the leading causes of irreversible visual impairment in the elderly, affecting hundreds of millions of patients. Müller glia cells (MGC), the main type of glia found in the vertebrate retina, can resume proliferation in the rodent adult injured retina but contribute weakly to tissue repair when compared to zebrafish retina. However, postnatal and adult mouse MGC can be genetically reprogrammed through the expression of the transcription factor (TF) Achaete-scute homolog 1 (ASCL1)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…The Müller glia has been gathering attention due to its proliferative properties after retinal injury and activation of stem/progenitor cell phenotype, allowing a return to the cell cycle and eventually differentiating into functional neurons. This has been shown for neurogenin 2 or ASCL1, transcriptional factors that, when nucleofected onto Müller glia, were reprogrammed into inducible neurons ( Guimaraes et al, 2018 ), functionally monitored in terms of calcium imaging. This strategy has been used by many groups to partially restore vision in different animal models ( Hampton, 2018 ).…”
Section: Retina a Central Modelmentioning
confidence: 92%
“…The Müller glia has been gathering attention due to its proliferative properties after retinal injury and activation of stem/progenitor cell phenotype, allowing a return to the cell cycle and eventually differentiating into functional neurons. This has been shown for neurogenin 2 or ASCL1, transcriptional factors that, when nucleofected onto Müller glia, were reprogrammed into inducible neurons ( Guimaraes et al, 2018 ), functionally monitored in terms of calcium imaging. This strategy has been used by many groups to partially restore vision in different animal models ( Hampton, 2018 ).…”
Section: Retina a Central Modelmentioning
confidence: 92%
“…Ectopic expression of NGN2 contributed to the production of a pool of neurons with expression of photoreceptor genes, amacrine cells, and ganglion layer cells. The authors also showed that the presence of mitogenic factors, such as EGF or bFGF, which stimulate the proliferation of mouse Müller glia cells increased the effectiveness of direct reprogramming (Guimarães et al, 2018). Proliferation is one of the passive ways to remove the methylation of DNA, epigenetic memory, which increases the effectiveness of direct reprogramming (Masserdotti et al, 2016;Kim and Costello, 2017).…”
Section: The Role Of Factors Of Cellular Specialization and Differentmentioning
confidence: 99%
“…Another highly plastic type of retinal cell, Müller glia cells, also has an intrinsic ability to be directly reprogrammed. Guimarães et al (2018) have shown that retinal ganglion cells in mice can be obtained from postnatal Müller glia cells by overexpression of NGN2. Ectopic expression of NGN2 contributed to the production of a pool of neurons with expression of photoreceptor genes, amacrine cells, and ganglion layer cells.…”
Section: The Role Of Factors Of Cellular Specialization and Differentmentioning
confidence: 99%
See 1 more Smart Citation
“…The search for ways to unlock this regenerative potential in mammals has increasingly attracted interest (Karl et al, 2008;Loffler et al, 2015;Ueki et al, 2015;Jorstad et al, 2017;Guimaraes et al, 2018;Yao et al, 2018). Pollak et al (2013) demonstrated that the overexpression of Ascl1 in Müller glia cultures and mouse retinal explants change gene expression with downregulation of glial genes and upregulation of progenitor genes.…”
Section: Regeneration From Endogenous Sources: Müller Gliamentioning
confidence: 99%